External Trade Bulletin of the ESCWA Region, Twentieth Issue - Nations Unies (United Nations, 2012)
This Bulletin presents data and statistical indicators on external trade in goods of ESCWA member countries. Data are presented in time series until 2010 and were drawn primarily from national sources, as well as from secondary sources where appropriate. The Bulletin comprises three parts: Part I on external trade statistics, Part II on intraregional trade, and Part III on the direction of trade. ESCWA hopes that this Bulletin, which provides total and detailed data on intraregional and international trade of member countries, would be useful to policymakers, analysts and researchers and other users at the national, regional and international levels.